Dampak Redenominasi Rupiah terhadap Penyajian Laporan Keuangan Audited - Muhammad Arsyad (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2023)
The purpose of this study is to see the impact of the redenomination of the rupiah on the presentation of audited financial statements. The research was conducted on auditors who work at Public Accounting Firms in Makassar. The data analysis method used is descriptive qualitative, the data collected from interviews will be processed and explained with reference to the literature study that has been done, then analyzed with three components, namely data reduction, data presentation and drawing conclusions. Based on the results of the research conducted, it can be seen that the rupiah redenomination policy will have an impact on simplifying financial calculations and reducing errors in financial transactions. carried out, as well as creating uniformity in simplifying the audited financial report assessment.